'He supported me 100%': Mexican-immigrant fathers, daughters, and adolescent sexual health. Issue 4 (18th May 2020) - Coleman-Minahan, Kate; Samari, Goleen
ABSTRACT: Objective: First and second generation Mexican-origin adolescents in the U.S. face social and economic disadvantage and sexual health disparities. Although fathers can support child and adolescent development, the literature has portrayed Mexican-origin immigrant fathers as emotionally distant and sexist. This study aims to treat migration as a social determinant of health to examine father-daughter relationships and adolescent sexual health in Mexican-origin immigrant families. Methods: Integrating qualitative data from life history interviews with 21 Mexican-origin young women in immigrant families with quantitative data on first and second generation Mexican-origin young women in the National Longitudinal Study of Adolescent to Adult Health, this study describes father-daughter relationships, examines the association between father-daughter relationships and daughters' early sexual initiation, and considers the impact of migration on the father-daughter relationship and sexual health among Mexican-origin young women. Results: Qualitative data identify four types of father-daughter relationships: 'good, ' hostile, distant, and conflicted. Supporting the qualitative patterns, quantitative data find that positive or 'good' father-daughter relationship quality is significantly associated with reduced risk of early sexual initiation. Importantly, father-daughter separation across borders and economic inequality facing immigrant families is associated with hostile or distant father-daughter relationship quality and increased risk of early sexual initiation. Conclusions: Reports of good father-daughter relationships are common and may protect against early sexual initiation in Mexican-origin immigrant families. Policies that keep families together and reduce economic inequality among immigrants may also reduce sexual health disparities among immigrant adolescents.